MEMPERJUANGKAN RUANG NEGOSIASI MELALUI PRODUKSI TEKS - medium, admin; Pramestisari, Nyoman Ayu Sukma (E-Jurnal Medium, 2022)
The plan to build the Benoa Bay reclamation mega project to support Bali's tourism industry. Ironically, the construction of reclamation has become a matter of controversy in the community because there have been various rejections through the ForBALI alliance. This can be seen from the production of the text of the article on the ForBALI.org page presenting the discourse of conflict between the counter-reclamation community and the government as a policy supporter as an oligarchy. Through the production of this text, periodical discourse is presented as well as reporting each case in detail along with an analysis of the critical dimensions of the counter-discourse community as resource persons, which are important points in attracting the sympathy of text consumers. Moreover, the sources in the text often have strong legitimacy because of their strategic position in society.